Strategic management from an Islamic perspective : text and cases - Fontaine, Rodrigue, 1970-; Ahmad, Khaliq (Singapore : Wiley, 2013)
Fascinating insights into modern strategic management from an Islamic perspective. While strategic management is a cornerstone of any MBA program, it's almost always taught from conventional theories and typically American case studies. This book takes those traditional theories and interprets them from an Islamic perspective using more international case studies. Though primarily intended as a textbook for business students, the book is also extremely useful for any Muslim business leaders who want to transform their businesses while complying with Shariah, with a particular focus on developing corporate cultures and structures in sync with Islamic values; Offers a critical review of conventional strategic management theory, suggesting more effective alternatives based on a combination of conventional and Islamic theories; Includes international case studies, each with a particularly Islamic angle; Written by a successful author team that has written extensively on the subject of business management from an Islamic perspective.--
pt. I. Strategy : an Islamic perspective -- pt. II. Case studies.
Includes bibliographical references and index.
Keywords: Management -- Islamic countries; Management -- Islamic countries -- Case studies; Management; Islamic countries; Electronic books; Case studies; Electronic books